2012
DOI: 10.1016/j.mce.2011.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of the human EAP1 gene is regulated by upstream components of a puberty-controlling Tumor Suppressor Gene network

Abstract: Mammalian puberty is initiated by an increased pulsatile release of gonadotropin-releasing hormone (GnRH) from specialized neurons located in the hypothalamus. GnRH secretion is controlled by neuronal and glial networks, whose activity appears to be coordinated via transcriptional regulation. One of the transcription factors involved in this process is thought to be the recently described gene Enhanced at Puberty 1 (EAP1), which encodes a protein with dual transcriptional activity. In this study we used gene r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4
1

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 58 publications
(110 reference statements)
0
14
0
Order By: Relevance
“…Using ChIP assays, we observed that all four of these transcription factors are recruited to the KiSS1 promoter; immunohistofluorescence studies showed that they are present in kisspeptin neurons in vivo (Mueller et al , 2011). We further observed that EAP1 gene expression is also under dual transcriptional regulation imposed by TTF1 (trans-activation) and YY1 and CUX1 (repression), and that EAP1 itself appears to control its own expression via a negative auto-feedback loop mechanism (Mueller and others, 2012). Consistent with the general features of a transcriptional regulatory network, TTF1, YY1 and CUX1 associate with the EAP1 promoter region and are expressed in hypothalamic EAP1 neurons, indicating that they are physiologically involved in the control of EAP1 gene expression.…”
Section: A Gene Network Controlling Pubertymentioning
confidence: 77%
“…Using ChIP assays, we observed that all four of these transcription factors are recruited to the KiSS1 promoter; immunohistofluorescence studies showed that they are present in kisspeptin neurons in vivo (Mueller et al , 2011). We further observed that EAP1 gene expression is also under dual transcriptional regulation imposed by TTF1 (trans-activation) and YY1 and CUX1 (repression), and that EAP1 itself appears to control its own expression via a negative auto-feedback loop mechanism (Mueller and others, 2012). Consistent with the general features of a transcriptional regulatory network, TTF1, YY1 and CUX1 associate with the EAP1 promoter region and are expressed in hypothalamic EAP1 neurons, indicating that they are physiologically involved in the control of EAP1 gene expression.…”
Section: A Gene Network Controlling Pubertymentioning
confidence: 77%
“…immortalized hypothalamic cells overexpressing EED. The ChIP procedure was carried out essentially as previously described (8,48,49). Supplementary…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that Eap1 transactivates the GnRH promoter but represses the preproenkephalin promoter, inferring that it has a dual transcriptional activity [4]. In 2012, Mueller et al [19]. discovered that Eap1 was regulated by ttf1, cux1 , and yy1 .…”
Section: Discussionmentioning
confidence: 99%